Risk factors for the conversion of laparoscopic to open cholecystectomy - Paidipelly, Kiran Kumar; ., Sangamitra (International Surgery Journal, 2018)
Background: Gall stones is one of the most common diseases in man. Laparoscopic cholecystectomy is the preferred procedure, mainly due to lower morbidity and mortality, thus returning to the normal activity sooner, lesser number of hospital days and lesser pain post-surgery. However, around 2-15% of the patients need to convert from laparoscopic to open surgery due to different reasons. Methods: 357 patients who came in for laparoscopic cholecystectomy were included into the study. Details such as age, height, weight, BMI, mode of surgery i.e. emergency or elective, physical and clinical examination including Ultrasound, lab results, previous history of surgery and other co morbidities were noted. Results: Out of the 357 patients, 31(8.7%) were converted to open cholecystectomies, of which, 61.3% females and 38.7% males. 58% in the open cholecystectomy group were above 60 years. 67.7% of the patients who converted to open surgery had a BMI of over 25, while it was 39.6% in case of laparoscopic surgery. 74.2% among the patients who had undergone conversion to the open surgery had pain in the right hypochondrium, 67.7% had increased WBC levels. Conclusions: Increased age, obesity, tenderness in the RHC, increased WBC levels, acute cholecystitis are the predisposing factors for the conversion of laparoscopic cholecystectomy to open cystectomy.